Peranan SDM Dalam Meningkatkan Kinerja Organisasi - Adelin Muldiawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to explore the role of human resources (HR) in improving organizational performance. Through literature analysis and case studies, this research highlights various factors and strategies that can be used by HR to improve organizational performance. It is hoped that the findings from this research will provide useful insights for HR managers in designing effective policies and practices in improving organizational performance.